2013
DOI: 10.1016/j.peptides.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pituitary Adenylate-Cyclase Activating Polypeptide and Tac1 gene derived tachykinins in sensory, motor and vascular functions under normal and neuropathic conditions

Abstract: a b s t r a c tPituitary Adenylate-Cyclase Activating Polypeptide (PACAP) and Tac1 gene-encoded tachykinins (substance P: SP, neurokinin A: NKA) are expressed in capsaicin-sensitive nerves, but their role in nociception, inflammation and vasoregulation is unclear. Therefore, we investigated the function of these neuropeptides and the NK 1 tachykinin receptor (from Tacr1 gene) in the partial sciatic nerve ligationinduced traumatic mononeuropathy model using gene deficient (PACAP −/− , Tac1 −/− , and Tacr1 −/− )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…The efficacy of triptans to attenuate both central (Kaiser et al, 2012) and peripheral CGRP-induced light aversion and motility in mice is consistent with the ability of triptans to reduce CGRPinduced migraine in humans (Asghar et al, 2011). Triptans are a family of antimigraine drugs that activate 5-HT1B/D receptors that induce vasoconstriction and inhibit the release of CGRP and other neuropeptides from nociceptors (Loder, 2010), including possibly inhibition of CGRP release by trigeminal afferents in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The efficacy of triptans to attenuate both central (Kaiser et al, 2012) and peripheral CGRP-induced light aversion and motility in mice is consistent with the ability of triptans to reduce CGRPinduced migraine in humans (Asghar et al, 2011). Triptans are a family of antimigraine drugs that activate 5-HT1B/D receptors that induce vasoconstriction and inhibit the release of CGRP and other neuropeptides from nociceptors (Loder, 2010), including possibly inhibition of CGRP release by trigeminal afferents in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Triptans are a family of antimigraine drugs that activate 5-HT1B/D receptors that induce vasoconstriction and inhibit the release of CGRP and other neuropeptides from nociceptors (Loder, 2010), including possibly inhibition of CGRP release by trigeminal afferents in this study. Despite being studied for Ͼ20 years, the sites of action of triptans remain controversial (Ahn and Basbaum, 2005), but the similar efficacy of various triptans regardless of their brain penetrance supports the importance of a peripheral site of action unless there is blood-brain barrier breakdown, which has yet to be demonstrated (Edvinsson and Tfelt-Hansen, 2008). In addition, the ability of sumatriptan to attenuate the effects of CGRP on both light aversion and motility suggests that these responses may be mediated by overlapping mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated miR-103 and miR-1a-3p modulate neuropathic or cancer pain through Cav1.2 calcium channel and clcn3, respectively [11], [28]. In the present study, the predicted target genes of miR-23a*, -24-2*, -26a, -92a, -125a-3p, -183, and -299, including NMDA, MAPK and Tac were found to be involved in neuropathic, inflammatory pain, or other states of pain [26], [32][34]. Furthermore, GO analysis indicated miR-125a-3p was involved in some processes of pain transduction including transmission of nerve impulse, synaptic transmission, regulation of action potential in neuron, regulation of inflammatory response and regulation of gene expression, which reminds us to pay more attention to it.…”
Section: Discussionmentioning
confidence: 50%
“…PACAP has a potent vasodilatory effect through the PAC 1 receptor and facilitates plasma leakage, edema formation, and leukocyte migration (). We have also shown that PACAP has a crucial role in the long‐term maintenance of neurogenic vasodilation on the periphery ().…”
mentioning
confidence: 90%